Comparison of Two Synthesis Methods for 3D PLA-Ibuprofen Nanofibrillar Scaffolds - Esteban Mena-Porras; Annaby Contreras-Aleman; María Francinie Guevara-Hidalgo; Esteban Avendaño Soto; Diego Batista Menezes; Marco Antonio Alvarez-Perez; Daniel Chavarría-Bolaños (Pharmaceutics)
Objectives: This study aimed to synthesize polylactic acid (PLA) nanofibrillar scaffolds loaded with ibuprofen (IBU) using electrospinning (ES) and air-jet spinning (AJS). The scaffolds were evaluated for their physicochemical properties, drug release profiles, and biocompatibility to assess their potential for local analgesic applications. Methods: Solutions of 10% (w/v) PLA combined with IBU at concentrations of 10%, 20%, and 30% were processed into nanofibrillar membranes using ES and AJS. The scaffolds were characterized using scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and Fourier-transformed infrared (FT-IR) spectroscopy. The drug release profile was assessed by ultraviolet-visible spectrophotometry (UV-Vis), and cell adhesion and viability were evaluated using fibroblast culture assays. Statistical analyses included qualitative analyses, t-tests, and Likelihood ratio tests. Results: SEM revealed randomly arranged nanofibers forming reticulated meshes, with more uniform dimensions observed in the AJS group. TGA and DSC analyses confirmed the thermodynamic stability of the scaffolds and enthalpy changes consistent with IBU incorporation, which FT-IR and UV-Vis validated. Drug release was sustained over 384 h, showing no significant differences between ES and AJS scaffolds (p > 0.05). Cytotoxicity and cell viability assays confirmed scaffold biocompatibility, with cellular responses proportional to drug concentration but within safe limits. Conclusions: PLA-IBU nanofibrillar scaffolds were successfully synthesized using ES and AJS. Both methods yielded biocompatible systems with stable properties and controlled drug release. Further, in vivo studies are necessary to confirm their clinical potential.